FREQUENCY OF CHRONIC SUPPURATIVE OTITIS MEDIA IN THE JUNIOR RANKS OF PAK ARMY: Chronic Suppurative Otitis Media - Iqbal, Javed; Khan, Waqar; Raza, Syed Nusrat; Naqvi, Nadeem Uddin; Rahat, Zahid Mehmood; Azeem, Qazi Ehsan; Hussain, Babar (Pakistan Armed Forces Medical Journal, 2009)
Objective:  The purpose of this study were to find out the frequency of chronic suppurative otitis media (CSOM) in the junior ranks of army, and to find out the number of such patients serving in low medical category due to CSOM. Study design: It was a simple multi-centre descriptive study. Place and Duration of Study: This study was conducted in ENT department of Combined Military Hospital Lahore from March 2003 to August 2003. Feedback was also taken from CMH Abbottabad and HIT Hospital Wah during this period. Subjects and Methods: A total of 5000 junior ranks were examined for CSOM. Results: Out of these 56 (1.12 %) were suffering from inactive mucosal disease. Seventy nine (1.58%) had active mucosal disease. Attico antral disease was present in 33 (0.66%) subjects and out of these 8 (0.16%) subjects had undergone mastoid exploration in the past. Ninety (1.8%) cases were serving in low medical category due to CSOM. Conclusion: The frequency of CSOM is significantly high in the army (03.36 %), considering that all inductions are made after initial medical examination. By observing few precautions the frequency may be reduced, thus decreasing the financial drain on national exchequer.